Pandangan Pejabat GBI Terhadap Covid-19 dan Vaksin dalam Bingkai Pemahaman tentang “Akhir Zaman” - Gernaida Krisna Pakpahan (KHARISMATA: Jurnal Teologi Pantekosta, 2022)
This study aims to determine the views of officials at the Indonesian Bethel Church (GBI) on Covid-19 in the perspective of the end of time. One of the important teaching points in Pentecostal theology is eschatology, which is characterized by wars between nations, natural disasters, famine, economic hardship, cruel leaders, disease, and false prophets, until the second coming of Christ. The phenomenon of the outbreak of the Covid-19 pandemic is a global epidemic that has infected millions of people in more than two hundred countries, and claimed many lives regardless of race, social status, age, education, nation, and other backgrounds. During the pandemic, economic difficulties are experienced globally, restrictions on social interaction, and changes in human life and cultural patterns. Another fact is that there are various views on the vaccination effort, some accept it and some reject it. The community of citizens who refuse vaccinations because of the fear that vaccines are a sign of the anti-Christ as in the book of Revelation. Starting from this background, a descriptive-analytical method will be used to obtain the results. In addition to conducting a biblical study, information was also obtained from 527 respondents who were GBI officials. The results are mixed, there are GBI officials who believe that Covid-19 is a sign of the end times, do not believe that Covid-19 is God's punishment for mankind, do not believe that it is the fulfillment of Revelation 9:7, believe that Covid-19 is a means of purification for mankind. God's church believes that vaccines are the way out to overcome Covid-19. AbstrakKajian ini bertujuan untuk mengetahui pandangan pejabat di Gereja Bethel Indonesia (GBI) terhadap Covid-19 dalam perspektif akhir zaman. Salah satu pokok ajaran penting dalam teologi Pentakostal adalah eskatologi, yang dikarakterisasi dengan adanya peperangan antar-bangsa, bencana alam, kelaparan, kesulitan ekonomi, pemimpin yang kejam, penyakit, nabi-nabi palsu, hingga kedatangan Kristus yang kedua. Fenomena merebaknya pandemi Covid-19 merupakan wabah global yang telah menginfeksi jutaan manusia di lebih dari dua ratus negara, merenggut banyak nyawa tanpa memandang ras, status sosial, usia, pendidikan, bangsa dan latar belakang lainnya. Selama pandemi kesulitan ekonomi dialami secara global, pembatasan interaksi sosial, dan perubahan pola kehidupan dan budaya manusia. Kenyataan lain ditemui pandangan yang beragam terhadap upaya vaksinasi, ada yang menerima dan ada juga yang menolak. Komunitas warga yang menolak vaksinasi karena adanya ketakutan bahwa  vaksin merupakan tanda anti-Kristus seperti dalam kitab Wahyu. Bertitik tolak dari latar belakang itu maka untuk memperoleh hasil akan digunakan metode deskritif analitis. Selain mengadakan kajian biblis juga diperoleh informasi dari 527 orang responden yang merupakan Pejabat GBI. Hasilnya beragam, ada pejabat GBI yang yakin bahwa Covid-19 merupakan tanda akhir zaman, tidak yakin bahwa Covid-19 adalah hukuman Allah bagi umat manusia, tidak yakin bahwa itu merupakan penggenapan dari Wahyu 9:7, meyakini Covid-19 sebagai sarana pemurnian bagi gereja Tuhan, dan menyakini vaksin adalah jalan keluar untuk mengatasi Covid-19.